Systematization of Nursing Care: a proposal for the organization of the Nursing Process in Primary Health Care - Souza, Érika de Almeida Leite da Silva Teixeira de (2021)
This study is an experience report that aims to describe the proposed adaptation of the Nursing Care Systematization (SAE) for Primary Health Care (PHC). Discussion groups were held with nurses from December 2018 to March 2019, using the SAE methodology, having as reference Cofen Resolution 358/2009, articulated with the Social Construction of PHC. The discussion was structured considering as axes: the articulation of the SAE with the social construction of the PHC; the definition of SAE methods, personnel processes and instruments in the APS. The SAE project in PHC was built, based on theories, to implement changes in the daily life of actions, articulating the macro and micro processes of PHC with care guided by the Nursing Process (NP), described in Data Collection, Diagnosis, Planning, Implementation and Assessment. The dimensioning, the organization of the scale, the training in carrying out the activities, procedures and the preparation and structuring of documents, technical-administrative and care records have potentialized nursing at the local level. Among the challenges, the need to build materials that can be replicated in training for the implementation of the SAE, the structuring of the NP record in the Electronic Medical Record and the standardization of a taxonomy to code nursing diagnoses was highlighted. The apprehension of these concepts by the team provoked concerns capable of generating new knowledge to induce adjustments in the SAE in PHC.